Does the subtype of breast cancer affect the diagnostic performance of axillary ultrasound for nodal staging in breast cancer patients?. Issue 4 (April 2019) - Vane, M.L.G.; van Nijnatten, T.J.A.; Nelemans, P.J.; Lobbes, M.B.I.; van Roozendaal, L.M.; Kooreman, L.F.S.; Keymeulen, K.B.M.I.; Smidt, M.L.; Schipper, R.J.
Abstract: Introduction: Imaging findings can be affected by histopathological characteristics, such as breast cancer subtypes. The aim was to determine whether the diagnostic performance, in particular negative predictive value (NPV), of axillary US differs per subtype of breast cancer. Methods: All patients diagnosed between 2008 and 2016 in our hospital with primary invasive breast cancer and an axillary US prior to axillary surgery were included. Histopathology of axillary surgery specimens served as gold standard. The NPV, sensitivity, specificity, positive predictive value (PPV) and accuracy of the axillary US were determined for the overall population and for each subtype (ER+/PR+HER2-, HER2+, triple negative tumors). The Chi-square test was used to determine the difference in diagnostic performance parameters between the subtypes. Results: A total of 1094 breast cancer patients were included. Of these, 35 were diagnosed with bilateral breast cancer, resulting in 1129 cancer cases. Most common subtype was ER+/PR+HER2- in 858 cases (76.0%), followed by 150 cases of HER2+ tumors (13.3%) and 121 cases of triple negative tumors (10.7%). Sensitivity, specificity and accuracy of axillary US did not significantly differ between the subtypes. There was a significant difference for NPV between triple negative tumors and HER2+ tumors (90.3% vs. 80.2%, p = 0.05) and between HER2+ and ER/PR+HER2- tumors (80.2% vs. 87.2%, p = 0.04). Conclusion: There was no significant difference in the diagnostic performance of axillary US between the subtypes, except for NPV. This was highest in triple negative subtype and lowest in HER2+ tumors. This can be explained by the difference in prevalence of axillary lymph node metastases in our cohort.